2006
DOI: 10.1007/s10202-005-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Rebound effects of progress in information technology

Abstract: Information technology (IT) is continuously making astounding progress in technical efficiency. The time, space, material and energy needed to provide a unit of IT service have decreased by three orders of magnitude since the first personal computer (PC) was sold. However, it seems difficult for society to translate IT's efficiency progress into progress in terms of individual, organizational or socio-economic goals. In particular it seems to be difficult for individuals to work more efficiently, for organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 9 publications
0
31
0
3
Order By: Relevance
“…Generally speaking, as less of a resource is needed to produce the output, the cost per unit of output becomes lower (in monetary terms, in terms of time or other types of effort) and the increased demand stimulated by the lower price may outweigh the resource reduction per unit [17,18]. In our conference example, the aim was to reduce travel energy demand and related emissions by offering two conference sites on different continents.…”
Section: System Boundariesmentioning
confidence: 99%
“…Generally speaking, as less of a resource is needed to produce the output, the cost per unit of output becomes lower (in monetary terms, in terms of time or other types of effort) and the increased demand stimulated by the lower price may outweigh the resource reduction per unit [17,18]. In our conference example, the aim was to reduce travel energy demand and related emissions by offering two conference sites on different continents.…”
Section: System Boundariesmentioning
confidence: 99%
“…These new aspects are: 4 Dematerialization effects of computing result in relevant reductions in energy consumption and greenhouse gas emissions, if not compensated by rebound effects [29,30]. 5 Embedded ICT hardware can also compromise established recycling processes [31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…The program first focused on substitution effects, such as electronic media substituted for print media [101], or videoconferencing substituted for travel [102] and their counteracting induction and rebound effects [103]. The chapter by Coroama, Moberg, and Hilty [88] in this volume provides an update on the substitution of electronic for traditional media.…”
Section: Energy Demand Throughout the Life Cycle Of Ict Devicesmentioning
confidence: 99%
“…In 2003, a controlled experiment was conducted that confirmed that increasing processing power of PCs was overcompensated for by new software versions in terms of user productivity, at least for the basic tasks of file handling and text editing. New versions of operating systems and text processors not only forced users to buy new PCs because of their higher demand of computing power (and therefore shortened lifetime of hardware), they also increased the time users would spend at the machine to perform the same task as before [103,113]. This trend, known as "software bloat", came to a temporary halt with the emergence of small mobile devices, in particular smartphones and tablets -thanks to the limitation of the energy density of their batteries.…”
Section: 6mentioning
confidence: 99%